Concomitant apical suspensory procedures in women with anterior vaginal wall prolapse in the United States in 2011 - Northington, Gina M.; Hudson, Catherine O.; Karp, Deborah R.; Huber, Sarah A. (International Urogynecology Journal, 2016)
Introduction Although the surgical restoration of apical support has been shown to decrease reoperation rates, it is unclear whether this has been incorporated into current practice. The aims of this study were to determine the rate of concomitant apical suspensory procedures in women with anterior vaginal wall prolapse undergoing surgical repair in 2011 and to identify associated factors. Methods This cross-sectional study queried the Nationwide Inpatient Sample for women with a primary diagnosis of cystocele who underwent prolapse repair in 2011. The study cohort was analyzed for demographics, concomitant procedures, and hospital characteristics. The rate of apical suspensory procedures was determined. Factors potentially associated with receiving concomitant apical suspensory procedure were evaluated using univariate analysis and multivariate logistic regression. Results A total of 2,900 women in the database had a primary diagnosis of cystocele and underwent surgical prolapse repair in 2011. 925 (31.9 %) subjects underwent a concomitant apical suspensory procedure. The mean age in the study cohort was 61.9 ± 12.8 years. Hysterectomies were performed in 11.1 % of subjects. 61.1 % were performed vaginally, 26.5 % laparoscopically, and 12.5 % abdominally. On multivariate analysis, age greater than 50 years, Caucasian race, concomitant hysterectomy, and an urban teaching hospital setting were independently associated with receiving concomitant apical suspensory procedure in 2011. Conclusions Despite evidence that the restoration of apical support is important for optimal anterior support, the overall rate of concomitant apical suspensory procedures is low. Several factors may play a role in whether or not women receive an apical suspensory procedure. This study highlights opportunities to improve the quality of surgical care provided to women with anterior vaginal prolapse.